2001
DOI: 10.2739/kurumemedj.48.307
|View full text |Cite
|
Sign up to set email alerts
|

Total Mesorectal Excision, Lateral Lymphadenectomy and Autonomic Nerve Preservation for Lower Rectal Cancer: Significance in the Long-term Follow-up Study.

Abstract: Summary: We clarify the significance of total mesorectal excision (TME), lateral lymphadenectomy (LLA), and of autonomic nerve preservation (ANP) compared to conventional surgery (CVS), for lower rectal cancer. All 458 patients curatively resected between 1962 and 1997 were retrospectively investigated. In Period I from 1962-1974, when CVS only was performed, in Period II from 1975-1984, THE or THE+LLA was performed, and in Period III from 1985-1997, THE+ANP, THE+ANP+LLA, or THE+LLA was performed. In Dukes A+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 37 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…However, the subgroup of patients with positive LLN can survive for more than five years after PSD. The reported five-year survival rates of patients with positive LLN ranged from 37.3 to 49.3 percent in each institute study, 31,32,[36][37][38][39][40] and the present study, which included a large number of patients, also showed the rate of 45.8 percent (Table 6).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, the subgroup of patients with positive LLN can survive for more than five years after PSD. The reported five-year survival rates of patients with positive LLN ranged from 37.3 to 49.3 percent in each institute study, 31,32,[36][37][38][39][40] and the present study, which included a large number of patients, also showed the rate of 45.8 percent (Table 6).…”
Section: Discussionsupporting
confidence: 53%
“…Table 6 summarizes the studies of PSD and positive LLN reported since 1996. [36][37][38][39][40] All except two 31,32 analyzed. The greater incidence of positive LLN of lower rectal cancer was observed by Ueno et al 40 and in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Shirouzu et al . from Japan compared local recurrence and survival after surgery using TME and BD with or without lateral lymphadenectomy (LLA), autonomic nerve preservation (ANP) or both [51]. Their results found that patients with Duke C cancer showed improvement with TME alone or in combination with LLA/ANP; 5‐year disease‐free survival also improved.…”
Section: Resultsmentioning
confidence: 99%
“…Lateral pelvic lymphadenectomy for advanced low rectal cancer is controversial [19][20][21][22][23][24][25] . In Japan, lateral pelvic lymphadenectomy is routinely performed for patients with advanced low rectal cancer, whereas it is not frequently performed in the Western countries [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%